Antimicrobial resistance in the main aquaculture resources of the departments of Tumbes, Piura, San Martin and Puno - Calizaya, Carla D (2023)
[Objective] The objective of this study was to analyze antimicrobial resistance in Peruvian aquaculture. [Methodology] An observational, descriptive study was carried out. Samples of Argopecten purpuratus, Oncorhynchus mykiss, Oreochromis niloticus and Litopenaeus vannamei were included. The bacteria Enterococcus spp., Salmonella spp., Escherichia coli, Vibrio parahaemolyticus, Aeromonas spp., and Flavobacterium psychrophilum were isolated. Antibiotic resistance was evaluated using antibiograms, and resistant samples were sequenced to identify antimicrobial resistance genes. Absolute and percentage frequencies were calculated. In addition, Wald, Clopper-Pearson, and pooled prevalence confidence intervals were estimated. [Results] In the case of A. purpuratus, 22.2% (95% CI:2.81-60.00) of the E. coli samples were resistant to oxytetracycline. Resistant samples were found in 4.44% (n=2) of the aquaculture production centers (APCs). In O. mykiss, 88.89% (95% CI:51.16-99.72) of the Enterococcus spp. were resistant to fosfomycin and oxytetracycline. Resistant samples were found in12.96% of the APCs (n=7). Regarding O. niloticus, 47.31% (95% CI: 37.16-57.46) of the E. coli samples were resistant to oxytetracycline>ampicilline>chloramphenicol>fosfomycin and azithromycin. Resistant samples were encountered in 50% of the APCs (n=19). In addition, 89.36% (95% CI:80.55-98.18) of the Enterococcus spp. were resistant to Fosfomycin> chloranphenicol and colistin> oxytetracycline>azithromycin>ampicilline; resistant samples were found in 36.84% of the APCs (n=14). In L. vannamei, 87.11% (95% CI:83.00-91.21) of the Enterococcus spp. samples were resistant to Fosfomycin> colistin> oxytetracycline> azithromycin>ampicilline and resistant samples were found in 100% of the APCs (n=33). Likewise, 35.05% (95% CI:29.74-40.23) of the V. parahaemolyticus samples were resistant to ampicilline>fosfomycin>oxytetracycline>azithromycin>eritromicine>enrofloxacin> ampicilline> chloranfhenicol. Resistant samples were found in 78.79% (n=26) of the APCs. [Conclusions] The percentage of APCs with O. niloticus and L. vannamei showed that antimicrobial resistance was high.